Upfront bortezomib, lenalidomide, and dexamethasone compared to bortezomib, cyclophosphamide, and dexamethasone in multiple myeloma. (7th July 2019) - Uttervall, Katarina; Borg Bruchfeld, Johanna; Gran, Charlotte; Wålinder, Göran; Månsson, Robert; Lund, Johan; Gahrton, Gösta; Alici, Evren; Nahi, Hareth
Abstract: Objectives: At our center, patients with multiple myeloma (MM) were treated upfront with bortezomib, cyclophosphamide, and dexamethasone (VCD) until cyclophosphamide was replaced with lenalidomide in the combination (VRD). These treatments have never been compared head‐to‐head in large real‐life patient material. Method: A retrospective analysis of patients treated with VRD and VCD in the first line, both with and without subsequent high‐dose treatment (HDT) and autologous stem cell transplantation. A total of 681 patients were included, 117 receiving VRD (71 with, 46 without HDT) and 564 receiving VCD (351 with, 213 without HDT). Results: Overall response rate (≥partial response) was higher with VRD compared to VCD in the entire VRD group (98% vs 88%, P  < 0.001) and in the non‐HDT group (98% vs 79%, P  < 0.001). Progression‐free survival (PFS) at 18 months was longer with VRD compared to VCD in the entire VRD group, the non‐HDT group and the HDT group (88% vs 63%, 82% vs 32% and 91% vs 73%, respectively). Overall survival at 18 months was better for VRD‐treated patients in the entire VRD group (95% vs 89%, P  = 0.048). Conclusion: Upfront VRD gives better responses and longer PFS compared to VCD in MM patients with or without subsequent HDT.